Shed female caribou antlers extend records of calving activity on the Arctic National Wildlife Refuge by millennia - Miller, Joshua H.; Wald, Eric J.; Druckenmiller, Patrick (Frontiers in Ecology and Evolution, 2023)
Caribou (Rangifer tarandus) have among the longest annual migrations of any terrestrial species as they move from winter ranges to spring calving grounds. Biomonitoring records indicate broad consistencies in calving geography across the last several decades, but how long have herds used particular calving grounds? Furthermore, how representative are modern patterns of calving geography to periods that pre-date recent climatic perturbations and increased anthropogenic stresses? While traditional ecological datasets are not long enough to address these questions, bones from past generations of caribou lying on the tundra provide unique opportunities to study historical calving geography. This is possible because female caribou shed their antlers within days of giving birth, releasing a skeletal indicator of calving activity. Slow Arctic weathering and bone recycling rates permit antlers to persist on landscape surfaces from centuries to millennia. Here, we present radiocarbon dates of three highly weathered antlers of female caribou collected from tundra surfaces on the Coastal Plain of the Arctic National Wildlife Refuge, Alaska. Today, the Arctic Refuge Coastal Plain is a key calving ground for the Porcupine Caribou Herd (PCH), which is among the world’s largest herds and a key resource for Native Gwich’in people in the US and Canada. Calibrated radiocarbon dates indicate that heavily weathered antlers evaluated here were shed between ~1,600 and more than 3,000 calendar years ago. The antiquity of these shed antlers provides the first physical evidence of calving activity on the PCH calving grounds from previous millennia, substantiating the long ecological legacy of the Coastal Plain as a caribou calving ground. Using lake core records, we also find that the dates of two of the antlers overlapped periods with summer temperatures that were anomalously high for the Holocene. This suggests that the Coastal Plain of the Arctic Refuge may remain an important calving ground for the PCH at least during portions of future warming. Discarded skeletal materials provide opportunities to assess the historical states of living populations and communities. Particularly in high-latitude settings, this insight can extend across millennia and offer rare glimpses into the past, which can inform current and future management policies.